Religion and Hezbollah: political ideology and legitimacy - Farida, Mariam (Routledge studies in Middle Eastern politics, 2019)
1. Historical Background 2. Fatwa and Politics 3. Hezbollah's Political Pragmatism Through Ijtihad 4. Social Mobilisation Theory 5. Content and Context Analyses of Nasrallah's Speeches 2000-2013 6. Hezbollah's Intervention in the Syrian Conflict: Insights and Implications 7. Conclusion